Operation performance of up-flow anaerobic sludge blanket (UASB) bioreactor for biohydrogen production by self-granulated sludge using pre-treated palm oil mill effluent (POME) as carbon source. (April 2019) - Mahmod, Safa Senan; Azahar, Azratul Madihah; Tan, Jian Ping; Jahim, Jamaliah Md; Abdul, Peer Mohamed; Mastar, Mohd Shahbudin; Anuar, Nurina; Mohammed Yunus, Mohammed Faisal; Asis, Ahmad Jaril; Wu, Shu-Yii
Abstract: Palm oil mill effluent (POME), an agro-industrial wastewater with high solids content, was subject to hydrolysis by 1% (w/v) nitric acid in order to increase its solubility and the fermentable sugar content from its cellulosic component. POME hydrolysate was then evaluated in an up-flow anaerobic sludge blanket (UASB) bioreactor for the production of biohydrogen gas via mixed culture under thermophilic conditions. The bioreactor was fed with pre-treated POME under varied hydraulic retention time (HRT) between 48 and 3 h at constant cycle length of 24 h to test the productivity of H2 and the stability of UASB; no washout of biomass occurred at any cycle and the system managed to recover its H2 production rate (HPR) after initial fluctuations. In this study, H2 -producing granules (HPGs) were formed shortly after the start-up period, and were analysed by FESEM, FTIR, SEM-EDX, and their extracellular polymeric substances (EPS) content. The maximum HY and HPR achieved were 2.45 mol-H2 /mol-sugar and 11.75 LH2 /LPOME d −1, respectively, at HRT 6 h. Acetic acid was found to be the major by-product at all HRTs, followed by butyric acid, while Clostridium spp . was found to be the most dominant H2 -producing bacteria in the system. Results suggest that UASB has a good potential for stable H2 production with high POME digestion rate. Graphical abstract: Highlights: Raw POME was pre-treated using dilute nitric acid. H2 -producing granules from POME were produced in UASB. Optimum biohydrogen yield achieved was 2.45 molH2 /molsugar . Bacterial community in H2 producing sludge was dominated by Clostridium spp.